A COGNITIVE APPROACH TO PROTOTYPICAL CASES OF BETWEEN-CLASS ZERO DERIVATION IN MACEDONIAN - Marjana Vaneva (European Scientific Journal, ESJ, 2013)
Zero Derivation is a type of word formation whereby from a lexeme that belongs to one lexical category or subcategory a new element is derived that has the same form (in the case with isolating languages) or similar form (with inflecting languages), similar or expanded meaning, and, what is most importantly, it is a member of a different word class or subclass. This process relies on cognition – the ability to understand things by connecting the new, unknown and inexperienced with the old, known and already experienced. The prototypical cases of zero derivation in Macedonian which illustrate formal overlapping between the starting and the resulting lexeme, and, in addition, their subgroup - between-class types will be analysed by showing that the direction of the process is between two classes at a time, that is, the process moves from a lexeme from one class to a lexeme in another class.